'Somebody stuck me in a bag of sand': Lived experiences of the altered and uncomfortable body after stroke. (September 2021) - Stott, Hannah; Cramp, Mary; McClean, Stuart; Turton, Ailie
Objective: This study explored stroke survivors' experiences of altered body perception, whether these perceptions cause discomfort, and the need for clinical interventions to improve comfort. Design: A qualitative phenomenological study. Setting: Participants' homes. Participants: A purposive sample of 16 stroke survivors were recruited from community support groups. Participants (median: age 59; time post stroke >2 years), were at least six-months post-stroke, experiencing motor or sensory impairments and able to communicate verbally. Interventions: Semi-structured, face-to-face interviews were analysed using an interpretive phenomenological approach and presented thematically. Results: Four themes or experiences were identified: Participants described (1) a body that did not exist; (2) a body hindered by strange sensations and distorted perceptions; (3) an uncontrollable body; and (4) a body isolated from social and clinical support. Discomfort was apparent in a physical and psychological sense and body experiences were difficult to comprehend and communicate to healthcare staff. Participants wished for interventions to improve their comfort but were doubtful that such treatments existed. Conclusion: Indications are that altered body perceptions cause multifaceted physical and psychosocial discomfort for stroke survivors. Discussions with patients about their personal perceptions and experiences of the body may facilitate better understanding and management to improve comfort after stroke.